Erosion Surface and Granitic Morphology in the Sierra de Lihuel Calel, Province of La Pampa, Argentina - Aguilera, Emilia Yolanda (2014)
Fil: Aguilera, Emilia Yolanda. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina